Humphry Davy and the Problem of Analogy. (3rd July 2019) - Tate, Gregory
Abstract : Analogy, the comparison of one set of relations to another, was essential to Humphry Davy's understanding of chemistry. Throughout his career, Davy used analogical reasoning to direct and to interpret his experimental analyses of the chemical reactions between substances. In his writing, he deployed analogies to organise and to explain his theories about the relations between physical processes and between the properties of different chemical elements and compounds. But Davy also regularly expressed two concerns about analogical comparison: first, that it was founded not on the rational interpretation of facts but on imaginative speculation; and second, that it was a kind of rhetoric, the persuasiveness of which depended not on material evidence but on misleading figures of speech. This article discusses the influences that informed Davy's ambivalent assessment of the value of analogy, and it examines the distinct yet overlapping ways in which this assessment was expressed in his notebooks, his lectures and treatises on chemistry, his philosophical writings, and his poetry.